THE IMPORTANCE OF PERSONAL MOTIVATION IN STUDENT VOLUNTEERING (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article examines the main factors and the actual importance of stimulating the student’s personal motivation in the volunteering of higher education students. Particular attention is paid to the specific characteristics of the motivation of young people to participate in voluntary activities. Concepts are provided to support and develop student volunteering.